Relapse rate after surgical treatment of maxillary hypoplasia in non-growing cleft patients: a systematic review and meta-analysis. Issue 4 (April 2020) - Jiang, L.; Zheng, Y.; Li, N.; Chen, X.; Lu, Z.; Tong, H.; Yin, N.; Song, T.
Abstract: Maxillary hypoplasia in cleft lip and palate is a complex deformity. Despite surgical improvements, postoperative relapse persists. This systematic review was performed to determine the mean horizontal relapse rates for the surgical techniques used to treat maxillary hypoplasia: Le Fort I osteotomy with rigid fixation, Le Fort I distraction osteogenesis, and anterior maxillary distraction osteogenesis. This study followed the PRISMA statement. The PubMed, Embase, Science Direct, and Web of Science databases were searched through to June 2018. Studies on non-growing cleft lip and palate patients who had undergone one of the three surgical procedures and who had postoperative horizontal maxillary changes assessed at >6 months post-surgery were included. Stata SE was used to estimate pooled means, heterogeneity, and publication bias. The search strategy identified 326 citations, from which 24 studies were selected. Relapse rates following Le Fort I osteotomy with rigid fixation, Le Fort I distraction osteogenesis, and anterior maxillary distraction osteogenesis were 20%, 12%, and 12%, respectively. Relapse rates with and without bone grafting were 19% and 66%, respectively. The relapse rate following distraction osteogenesis with internal distraction was lower than that with external distraction. Study limitations were heterogeneity, which was above moderate, the low number of high-quality studies, and unidirectional assessment of postoperative maxillary movement.